Supraclavicular Brachial Plexus Block with or Without Dexamethasone as an Adjuvant to 0.5% Levobupivacaine - Kumar, Rakesh; Danda, Tarun Kumar; Tandon, Atul (Academia Anesthesiologica International, 2020)
Background: Brachial plexus block is good alternative to general anesthesia for upper limb surgery. The present study was conducted to assess supraclavicular brachial plexus block with or without dexamethasone as an adjuvant to 0.5% levobupivacaine. Subjects and Methods: 40 patients in the age group of 18-60 years were randomly divided in two groups of 20 patients. In group I, patients received 30 ml of 0.5% isobaric levobupivacaine with 2 ml of isotonic sodium chloride. In group II patients received 8 mg (2ml) dexamethasone in addition to 30 ml of 0.5% isobaric levobupivacaine. Results: The mean onset of sensory block was 10.4 minutes in group I and 8.1 minutes in group II, onset of motor blockade was 15.6 minutes in group I and 13.2 minutes in group II, duration of sensory blockade was 620.4 minutes in group I and 914.8 minutes in group II, duration of motor blockade was 542.6 minutes in group I and 712.6 minutes in group II and total analgesic requirement was seen in 22 minutes in group I and 4 patients in group II. The difference was significant (P< 0.05). Conclusion: Dexamethasone reduced the time to onset of sensory and motor blockage and prolongs the duration of analgesia.